Pre-service mathematics teachers TPACK development in a computer-assisted mathematics instruction course - Erdoğan, Nazmi. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2014., 2014)
In Turkey there is a policy to integrate technology into education. Classrooms have been equipped with interactive white boards, internet networks, and tablet computers. In this process, it is essential for pre-service teachers to know how to use technology for educational purposes. The aim of this thesis is to investigate pre-service mathematics teachers‟ technological, pedagogical, and content knowledge (TPACK) development in a computer assisted mathematics course. The need to train pre-service teachers as capable of using technology for teaching makes this research important. This research was based on collection and analysis of both quantitative and qualitative data. Qualitative part of this research was a case study. Quantitative data were collected from 29 pre-service teachers with a TPACK Survey. Qualitative data were collected from 6 pre-service teachers by interviewing and observing throughout the course. Findings from this research show that it is possible for a university course to develop pre-service teachers‟ TPACK and this development is related to given technology, various personal factors of pre-service teachers, group work among them, and the structure of the course. This thesis presents recommendations regarding content specific technology related courses and collaboration among pre-service teachers in these courses in order to support their TPACK development.
Keywords: Educational technology.; Education -- Effect of technological innovations on.; Teachers -- Training of.; Mathematics teachers.